SHORT TERM EFFECT OF DOSE DEPENDENT CAMEL MILK IN ALLOXAN INDUCED DIABETES IN FEMALE ALBINO RATS - M. Usman; M. Z. Ali; A. S. Qureshi; M. K. Ateeq; F. U. Nisa (Journal of Animal and Plant Sciences, 2018)
Current project was designed to evaluate the antidiabetic effect of camel milk on hematology, serum profile and histology of selected organs. Forty female albino rats were divided into 4 groups ( n=10) : Group 1 as placebo. Diabetes ® was induced by Alloxan in remaining groups. Group 2 served as diabetic control while group 3 and 4 were offered camel milk orally @ 20 and 40ml/kg/day, respectively, for 60 days. Weekly blood glucose was measured. Animals were slaughtered on day 60 to collect: blood for hematology and tissue for histology. Microscopy was done for degenerative changes in uterus (epithelial height, gland area, thickness of endometrium and myometrium), liver and kidneys. Diabetes revealed significant (P<0.05) adverse effect on all parameters. Camel milk exhibited more significant (P<0.05) mitigating influence on diabetic altered hematology and histology of uterus, liver and kidney @ 40ml/kg compared to 20 rd ml/kg. Camel milk @ 20 ml/kg significantly (P<0.05) reduced blood glucose in 3 week and remained constant in trial nd while this reduction was significant (P<0.05) at 2 week and became more significant (P<0.01) in last two weeks @ 40 ml/kg. Hence, camel milk has potential to recover elevated blood glucose, hematological parameters and degenerative changes in uterus, liver and kidneys. 1 DM has perturbative impact on the ovarian steriogensis,
Keywords: camel milk; diabetes; uterus; hematology; microscopy; liver function test; kidney.